Community coalitions as a tool for fostering participatory development in urban informal settlements - El-Sayeh, Salma (AUC Knowledge Fountain, 2013)
It is estimated that Greater Cairo has pushed 63% of its population –11 million citizens – into informal settlements. Past governmental and non-governmental efforts to deal with informal settlements have not produced any sustainable changes in the situation of the urban poor. The current study explores the applicability of community coalition building – a participatory, empowering and transformative community building tool – for the development of urban informal settlements. By studying one of greater Cairo’s informal settlements, the study attempts to answer three research questions: 1) What is the state of meso level social capital in the selected informal settlement?, 2) What are the motivators, de-motivators of, and relevance of coalition building among the network of stakeholders within the informal settlement? and, 3) What is the preferred structure and strategy for coalition building among the network of stakeholders within the informal settlement? Results are based on interviews with top management representatives of voluntary and involuntary organizations mobilizing for one of Greater Cairo’s informal settlements development. Social network analysis was used to identify collaborative and communicative links across the network. Moreover, qualitative results were analyzed against the Community Coalition Action Theory to generate practical and community driven recommendations for coalition building within the area. Results indicated a mixture of significant assets and obstacles to coalition building. Practical recommendations are made for utilizing identified assets and overcoming identified obstacles to realize informal settlements’ community capacity through coalition building.